A review on bioremediation of pulp and paper mill effluent – An alternative to conventional remedial technologies (Journal of Applied and Natural Science, 2018)
At present, a large amount of water required for paper production and various chemicals has been identified in effluents, which is produced at different steps of paper making in paper mills. The pulp and paper industry is typically related to pollution difficulties related to high biological oxygen demand (BOD), chemical oxygen demand (COD), colour, suspended solids, lignin and chlorinated compounds. Several studies have been made on eliminate these difficulties of pulp and paper effluents, the problem still continues. Although the physical and chemical methods are on the track of treatment, they are not on par with biological treatment because of cost ineffectiveness and residual effects. The biological treatment is known to be effective in reducing the organic load and toxic effects of paper mill effluents. Some microorganisms including bacteria and fungi have been involved in degrading the chemicals present in pulp and paper mill effluent. This article is an overview of the attempts made by several researchers worldwide to use biotechnological methods for degradation of the toxic compounds present in pulp and paper mill effluents by using fungi, bacteria, algae and enzymes. The current study clearly shows that application of native dominant bacterial and fungal isolates may be used forthe treatment of large pulp and paper mills effluents.